Universal Design is “not only” a Design for People with Disabilities - Pujiyanti, Indah; Ikaputra (Departement of Architecture, Universitas Islam Indonesia, 2025)
Universal design is an approach that aims to create products, buildings, environments and services that are inclusive and accessible to everyone, regardless of age, gender or physical ability. In its development, universal design has been widely used in planning and architectural design. This research aims to discover how the development of the universal design paradigm from its inception identifies the pros and cons of applying universal design. This research hopes to explain the correct position of universal design for architects and policymakers so that there is an increase in the quality realization of accessibility/elements of universal design that is improving. The method used in this study is to examine various sources of journal articles that are relevant to universal design theory. Through a comprehensive literature analysis, the results of this study found that the origin of universal design stemmed from the development of the concept of barriers, which changed the perception of exclusivity to inclusivity. In addition, several benefits of implementing universal design are known in the form of long-term investment, economic value, and support for sustainable design. Keywords: Architecture; Barrier-Free; Disabled; Paradigm; Universal Design